2022
DOI: 10.1021/acs.est.1c08771
|View full text |Cite
|
Sign up to set email alerts
|

Does the Geographic Difference of Soil Properties Matter for Setting Up the Soil Screening Levels in Large Countries Like China?

Abstract: China issued the unified national soil screening levels (NSSLs) in 2018 to assist the regulation of contaminated sites, but the applicability of NSSLs was not thoroughly evaluated. Datasets from the National Qinghai–Tibet Plateau Scientific Data Center indicated great variability of soil organic matter (0.8–173 g/kg), soil water content (0.05–0.6), soil porosity (0.4–0.6), and soil bulk density (1.11–1.59 kg/m3). We analyzed the effects of soil properties on the derivation of SSLs by using Monte Carlo simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…3,4 In China, according to the National Soil Contamination Survey Bulletin published in 2014, around 16% of surveyed soil samples had at least one organic pollutant exceeding standard values, particularly the organohalide pollutants. 5 Similarly, an agricultural soil survey reported that volatile organohalides were present in all tested samples. Among them, chloroethenes (CEs) detection frequency ranged from 3.57 to 6.25%, with a concentration range from 0.9 to 3.61 ng/g.…”
Section: ■ Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…3,4 In China, according to the National Soil Contamination Survey Bulletin published in 2014, around 16% of surveyed soil samples had at least one organic pollutant exceeding standard values, particularly the organohalide pollutants. 5 Similarly, an agricultural soil survey reported that volatile organohalides were present in all tested samples. Among them, chloroethenes (CEs) detection frequency ranged from 3.57 to 6.25%, with a concentration range from 0.9 to 3.61 ng/g.…”
Section: ■ Introductionmentioning
confidence: 90%
“…14 CE attenuation. 15,16 However, the soil organic and mineral compositions, as well as their biophysiochemical properties, could be highly variable, e.g., organic matter (0.8−173 g/kg), water content (0.05−0.6 m 3 m −3 ), porosity (40−60%), and bulk density (1.11−1.59 kg/m 3 ), 5 posing challenges in understanding the major players and their specific roles in abiotic attenuation of organohalides. In addition to these abiotic compositions and processes, microorganisms also played critical roles in removing organohalides.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies on soil pollution source analyses have shown that industrial and mining enterprise sewage disposal activity has become the main source of soil pollution and risk in China [9][10][11][12]. According to the 2014 national survey report on soil contamination, the soil exceedance rate around industrial and mining enterprises was 36.3%, which was much higher than that of the total samples throughout China (16.1%) [13][14][15]. Soil contamination was particularly prominent in some regions, such as the northeastern old industrial base [16,17].…”
Section: Introductionmentioning
confidence: 99%